Reorientasi Peran dan Fungsi Guru di Era Globalisasi - Maharani Dwi Nurhalizah Rahmah; Inayah Thohiroh; Muhammad Rivaldi; Mimah Mahmudah; Jamal Abu Rizal (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
The era of globalization has brought significant changes to the world of education, particularly to the role and function of teachers in the learning process. Advances in information technology and easy access to knowledge require teachers to reorient their roles from mere transmitters of material to facilitators, motivators, curators of information, and mentors of student character. This study aims to examine the nature of the reorientation of the role and function of teachers in the era of globalization, the reasons for the need for such changes, the ideal form of teacher roles, and the challenges and strategies in their implementation. The research method used is a qualitative approach with a literature study through analysis of various books, journals, and relevant scientific sources. The results show that the reorientation of teacher roles is necessary due to changes in learning paradigms, technological developments, and the demand for 21st-century skills. However, the process still faces various challenges such as low digital literacy, conventional mindsets, limited training, and a lack of infrastructure support and parental participation. Therefore, strategies are needed such as improving teacher professional development, strengthening digital literacy, simplifying administrative burdens, and strengthening cooperation between schools, parents, and the community. With this reorientation, it is hoped that teachers will be able to play an optimal role in improving the quality of education and developing a generation that is intelligent, has character, and is ready to face global challenges.